Effects of drug concentration and PLGA addition on the properties of electrospun ampicillin trihydrate-loaded PLA nanofibers - Eren Böncü, Tuğba; Ozdemir, Nurten (Beilstein Journal of Nanotechnology, 2022)
The aim of this study was to produce ampicillin trihydrate-loaded poly(lactic acid) (PLA) and PLA/poly(lactic-co-glycolic acid) (PLA/PLGA) polymeric nanofibers via electrospinning using 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) as the solvent for local application in tissue engineering. The effects of ampicillin trihydrate concentration (4–12%) and addition of PLGA (20–80%) on the spinnability of the solutions, morphology, average nanofiber diameter, encapsulation efficiency, drug release, and mechanical properties of PLA and PLA/PLGA nanofibers were examined. All nanofibers were bead-free and uniform. They had favorable encapsulation efficiency (approx. 90%) and mechanical properties. The increase in the amount of ampicillin trihydrate caused an increase in the diameter and burst effect of the nanofibers. The drug release ended on the 7th and 3rd day with nanofibers containing 4% and 12% of drug, respectively. The prolonged and controlled drug release for ten days was obtained with nanofibers containing 8% of drug. Thus, the ideal drug concentration was determined to be 8%. Nanofibers containing PLA/PLGA had a larger diameter than those including PLA. In addition, both the strength and elongation of nanofibers decreased depending on the increase in nanofiber size with the addition of PLGA, increased amount of drug, and ratios of PLGA. Drug release studies showed that PLA/PLGA nanofibers exhibited a lower burst effect and a decrease in drug release when compared to PLA nanofibers. Finally, PLA/PLGA nanofibers can be produced with enhanced encapsulation efficiency and mechanical properties, resulting in controlled and tailored release of ampicillin trihydrate for at least ten days. In conclusion, it was demonstrated that the addition of PLGA in different ratios and the amount of drug can be manipulated to obtain the desired properties (average nanofiber diameter, morphology, in vitro drug release, and mechanical properties) of PLA nanofibers.
Keywords: ampicillin trihydrate; electrospinning; nanofiber; PLA nanofiber; PLA/PLGA nanofiber